Colloidal lithography nanostructured Pd/PdOx core–shell sensor for ppb level H2S detection. (25th April 2018) - Benedict, Samatha; Lumdee, Chatdanai; Dmitriev, Alexandre; Anand, Srinivasan; Bhat, Navakanta
Abstract: In this work we report on plasma oxidation of palladium (Pd) to form reliable palladium/palladium oxide (Pd/PdO x ) core–shell sensor for ppb level H2 S detection and its performance improvement through nanostructuring using hole-mask colloidal lithography (HCL). The plasma oxidation parameters and the sensor operating conditions are optimized to arrive at a sensor device with high sensitivity and repeatable response for H2 S. The plasma oxidized palladium/palladium oxide sensor shows a response of 43.1% at 3 ppm H2 S at the optimum operating temperature of 200 °C with response and recovery times of 24 s and 155 s, respectively. The limit of detection (LoD) of the plasma oxidised beam is 10 ppb. We further integrate HCL, a bottom-up and cost-effective process, to create nanodiscs of fixed diameter of 100 nm and varying heights (10, 15 and 20 nm) on 10 nm thin Pd beam which is subsequently plasma oxidized to improve the H2 S sensing characteristics. The nanostructured Pd/PdO x sensor with nanodiscs of 100 nm diameter and 10 nm height shows an enhancement in sensing performance by 11.8% at same operating temperature and gas concentration. This nanostructured sensor also shows faster response and recovery times (15 s and 100 s, respectively) compared to the unstructured Pd/PdO x counterpart together with an experimental LoD of 10 ppb and the estimated limit going all the way down to 2 ppb. Material characterization of the fabricated Pd/PdO x sensors is done using UV–vis spectroscopy and x-ray photoemission spectroscopy.